Adeno-associated viral vectors expressing anti-HBV TALENs from an mTTR promoter - Jacobs, Ridhwaanah (My University, 2019)
Abstract Hepatitis B virus (HBV) infection is a major public health concern accounting for 2 billion infections world-wide. HBV infection results in acute and chronic liver disease as well as Hepatocellular carcinoma. The HBV genome contains four overlapping open reading frames (ORFs) S, C, P and X. The S ORF encodes for the HBsAg and is one of the first viral markers to be detected in the serum of an infected individual. Upon infection with HBV, the viral genome is transported to the nucleus, where it is repaired to covalently closed circular DNA (cccDNA). The cccDNA serves as a template for the transcription of viral RNA and translation of viral proteins. Several drugs have been developed to target HBV, but they are not effective in eliminating the cccDNA, which results in relapse following treatment. This has paved the way for designer nucleases such as Transcription activator-like effector nucleases (TALENs) to be explored in targeting cccDNA. TALENs induce double stranded breaks (DSBs) within the viral DNA. The DSBs are repaired by error prone Non-homologous end joining (NHEJ), which results in insertions and deletions. In a study conducted by the Antiviral Gene Therapy Research Unit (AGTRU), anti-HBV TALENs were designed to target the ORFs of the HBV genome. A higher percentage of targeted mutagenesis was observed when using TALENs targeting the S ORF. To improve the effectiveness and efficiency of the anti-HBV TALENs, these TALENs were expressed from a liver-specific murine transthyretin promoter (mTTR) in this study. A major obstacle of the translation of this therapeutic to the clinic is the lack of a safe and efficient delivery vehicle. Adeno-associated viral vectors (AAVs) are a promising gene delivery vehicle as they are non-pathogenic, have high transduction efficiency and can transduce a variety of cell types. Thus far, no study has investigated the ability of AAVs to deliver anti-HBV TALENs. In this work, AAV genome bearing plasmids were successfully engineered to express anti-HBV TALENs from an mTTR promoter. An in-depth characterization of these plasmids demonstrated that the anti-HBV TALENs achieved over 80 % gene silencing and 5.89 % detectable targeted mutagenesis without any toxic effects. These plasmids were then used to produce viral vectors containing anti-HBV TALEN encoding sequences. The viral vectors were able to achieve 55 % gene silencing at day 2 post transduction. No toxicity to the viral vectors used was detected. This is the first study to identify AAVs as a delivery vehicle for anti-HBV TALENs and will contribute significantly to the progression of these nucleases into the clinic.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Medicine, Johannesburg, 2019